Bioinspired Phototropic MXene‐Reinforced Soft Tubular Actuators for Omnidirectional Light‐Tracking and Adaptive Photovoltaics (Adv. Funct. Mater. 26/2022). (24th June 2022) - Yang, Mengyuan; Xu, Yiyi; Zhang, Xuan; Bisoyi, Hari Krishna; Xue, Pan; Yang, Yanzhao; Yang, Xiao; Valenzuela, Cristian; Chen, Yuanhao; Wang, Ling; Feng, Wei; Li, Quan
Abstract : Adaptive Photovoltaics In article number 2201884, Ling Wang, Wei Feng, Quan Li, and co‐workers report bioinspired phototropic MXene‐reinforced soft tubular actuators exhibiting omnidirectional self‐orienting and light‐tracking capability. An adaptive photovoltaic system with solar energy harvesting maximization is conceptualized by integrating the soft tubular actuator with commercially available solar panels.